2008
DOI: 10.1063/1.2899939
|View full text |Cite
|
Sign up to set email alerts
|

Grain refinement assisted strengthening of carbon nanotube reinforced copper matrix nanocomposites

Abstract: Carbon nanotube reinforced copper matrix ͑CNT/Cu͒ nanocomposites were fabricated by the modified molecular-level mixing process, which produces a homogeneous dispersion of CNTs in a fine grained metal matrix. These nanocomposites, consisting of 1.5 m Cu matrix grains and 5 vol % of multiwall CNTs, show a high strengthening capability; enhancing the yield strength of unreinforced Cu by 2.3 times. The enhanced yield strength stems from the reinforcing effect of CNTs and additional hardening of the Cu matrix by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 20 publications
5
59
0
Order By: Relevance
“…This is evident from the earlier research studies, the tensile load exerted on the composite transferred to the carbon nanotube thereby pulling leads to bending in nanotubes and break in the form of telescopic sheath [33,34]. The effective dispersion and better interfacial bonding between the matrix and the varied fraction of MWCNTs enhanced the UTS as reported by the others [35,36].…”
Section: Tensile Testsupporting
confidence: 51%
See 1 more Smart Citation
“…This is evident from the earlier research studies, the tensile load exerted on the composite transferred to the carbon nanotube thereby pulling leads to bending in nanotubes and break in the form of telescopic sheath [33,34]. The effective dispersion and better interfacial bonding between the matrix and the varied fraction of MWCNTs enhanced the UTS as reported by the others [35,36].…”
Section: Tensile Testsupporting
confidence: 51%
“…Fracture micrographs of the Al2024+MWCNT composite displayed the resistance nature of nanotubes ( Figure 8c) by way of deformation. The breaking of the material for the applied force due to which matrix pulls out and nanotubes breaks in telescopic sheath form as reported by Bakshi et al [35]. Bent nanotubes promote increase young's modulus during applied tensile load and are rigid in nature [30].…”
Section: Tensile Testmentioning
confidence: 81%
“…Previous studies indicated characteristics of the metal matrix composites (MMCs) reinforced with CNTs, where industrial metals such as aluminum, magnesium, nickel, copper and their alloys were used [5][6][7][8][9][10][11][12][13][14]. Titanium (Ti) and titanium alloy are also interested as the matrix material because they are widely used in various industrial applications, for example, automotive, motorcycles, and airplane industries due to their high specific strength and Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Cu and CNT-Cu cylinders (diameter 8 mm and length 33 mm) were prepared by SPS (PNF 2 -Toulouse, Dr. Sinter 2080, SPS Syntex Inc., Japan) using 8 mm inner diameter WC/Co dies according to a procedure described elsewhere [12], changing only the heating rates: 25°C·min No phase change such as carbide formation was detected by X-ray diffraction in agreement with other works [13,16,17]. The cylinders relative density (Archimedes' method) is equal to 94 ± 1% (U samples) and 88 ± 2% (B samples).…”
Section: T R a C Tmentioning
confidence: 50%